Using achievement tests to measure language assimilation and language bias among immigrant children - Richard Akresh; Ilana Redstone Akresh (Institute for the Study of Labor (IZA), 2008)
We use Woodcock Johnson III child assessment data in the New Immigrant Survey to examine language assimilation and test score bias among children of Hispanic immigrants. Our identification strategy exploits the test language randomization (Spanish or English) to quantitatively measure the degree and speed of language assimilation, in addition to the potential costs associated with taking a test in ones non-dominant language. We find that U.S. born children of Hispanic immigrants are not bilingual as predicted by most language assimilation models but rather are English dominant. English language assimilation occurs at a rapid pace for foreign born children as well; children who arrive in the U.S. at an early age or who have spent more than four years in the U.S. do not benefit from taking the tests in Spanish. Results are robust to a fixed effects specification that controls for household level characteristics constant across siblings.
urn:nbn:de:101:1-20080609133
Keywords: J24; 300; Immigration; language assimilation; New Immigrant Survey; Woodcock Johnson achievement tests; Kinder; Migranten; Mehrsprachigkeit; Soziale Integration; Englisch (Sprache); Spanisch; Hispano-Amerikaner; USA